2004
DOI: 10.1088/0029-5515/44/5/011
|View full text |Cite
|
Sign up to set email alerts
|

On the form of NTM onset scalings

Abstract: Theoretically, the normalized plasma pressure (β) at which a neoclassical tearing mode (NTM) is triggered is expected to depend on normalized Larmor radius (ρ*) and normalized collisionality (ν), and this has formed the basis for the way in which NTM onset scalings are quoted for many devices. However, new analyses of JET data show that such ρ*–ν based scalings are non-predictive, with discharges largely following such scalings over the majority of their duration while in H-mode. Neural network techniques indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 23 publications
(44 reference statements)
4
46
0
Order By: Relevance
“…In other words, the triggering of NTMs in a device is not directly linked to the b levels but to the mechanisms which generate seed islands. 4 Previous research has identified several different causes for the formation of seed islands such as an unstable tearing mode, [5][6][7] MHD events such as sawtooth 8 and fishbones, 9 error fields, 10,11 edge localized modes (ELMS), 12 nonlinear mode coupling, 13 and turbulence. 14,15 This diversity of origins poses serious challenges for experimentally anticipating their appearance and choosing appropriate control parameters for their avoidance and suppression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the triggering of NTMs in a device is not directly linked to the b levels but to the mechanisms which generate seed islands. 4 Previous research has identified several different causes for the formation of seed islands such as an unstable tearing mode, [5][6][7] MHD events such as sawtooth 8 and fishbones, 9 error fields, 10,11 edge localized modes (ELMS), 12 nonlinear mode coupling, 13 and turbulence. 14,15 This diversity of origins poses serious challenges for experimentally anticipating their appearance and choosing appropriate control parameters for their avoidance and suppression.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 This diversity of origins poses serious challenges for experimentally anticipating their appearance and choosing appropriate control parameters for their avoidance and suppression. 4 Present experimental efforts towards the control of NTMs rely primarily on tracking the appearance of seed islands at various mode rational surfaces and preventing their growth by replacing the missing bootstrap current inside them through externally driven helical currents. This can be achieved, for instance, by the generation of non-inductive current through the injection of radio frequency or electron cyclotron waves into the plasma (electron cyclotron current drive or ECCD).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst one of the reasons for adopting the weak shear q-profile was that it is predicted to be significantly more stable to fast ion-driven instabilities than strongly reversed shear plasmas with higher q 0 [31], it is nonetheless important to consider the implications of energetic particle modes for plasma confinement. It is still important to keep q > 1 though, since the significant fast ion population in DEMO would probably result in very long sawtooth periods [56,57], which are more likely to trigger deleterious NTMs [58][59][60] which in turn degrade confinement and can disrupt the plasma. Similarly, it has been shown recently that kinetic effects can substantially alter RWM stability [20,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of an effective actuator to shorten the sawtooth period, coupling can occur with instabilities located at rational surfaces outside the q = 1 surface -the location of the sawtooth instability. Furthermore, it has been shown in the Joint European Torus (JET) that long sawteeth are more likely to trigger performance-degrading neoclassical tearing modes (NTMs) at lower plasma pressures [6,7]. Conversely, improved confinement is often coincident with smaller, regular sawteeth, which have the ancillary benefit of preventing accumulation of impurities in the plasma core [8].…”
Section: Introductionmentioning
confidence: 99%